The Arab Spring : ten years on - Ashwarya, Sujata; Alam, Mujib (Middle Eastern Studies., 2022)
It has been more a decade since people across the Arab world rose up in revolt against their governments, demanding political empowerment, social reform and economic improvement. Pro-democracy protests, as they were called in common parlance, which spread rapidly through the mobilisation of social media calls, ended up overthrowing long-standing authoritarian regimes in Tunisia, Egypt, Yemen and Libya. That gave rise to hope for a more representative future, a.